Retraction notice to “Unveiling Iranian courtyard house: the example of Kuy-e Chaharsad-Dastgah (1946–1950)” [Journal of Architecture and Urbanism, 43(1), 91-111, 2019] - Sedighi, Mohamad; van Gameren, Dick (Journal of Architecture and Urbanism, 2020)
The following article is being retracted from publication in Journal of Architecture and Urbanism: Unveiling Iranian courtyard house: the example of Kuy-e Chaharsad-Dastgah (1946–1950) authored by Mohamad Sedighi and Dick van Gameren, Volume 43, Issue 1, pp. 91–111, Journal of Architecture and Urbanism, 2019. https://doi.org/10.3846/jau.2019.6046 https://journals.vgtu.lt/index.php/JAU/article/view/6046 Received 09 October 2018; accepted 04 April 2019 In the mentioned article, there are some overlaps with some of the ideas presented in the article by Rana Habib “ The institutionalization of modern middle class neighborhoods in 1940s Tehran – Case of Chaharsad Dastgah”. The authors accepted to withdrew their article, as the republication of their article with a new title and some changes in the structure was not to be considered minor revision by Journal of Architecture and Urbanism. The Editors and publishers of the journal, Vilnius Gediminas Technical University, note that we received, peer-reviewed, accepted and published the article on the basis that the authors are presenting original results. The retracted article will remain online to maintain the scholarly record, but it will be digitally watermarked on each page as “retracted”.